Form and motion coherence activate independent, but not dorsal/ventral segregated, networks in the human brain. - Braddick, O; O'Brien, J; Wattam-Bell, J; Atkinson, J; Turner, R (2000)
There is much evidence in primates' visual processing for distinct mechanisms involved in object recognition and encoding object position and motion, which have been identified with 'ventral' and 'dorsal' streams, respectively, of the extra-striate visual areas [1] [2] [3]. This distinction may yield insights into normal human perception, its development and pathology. Motion coherence sensitivity has been taken as a test of global processing in the dorsal stream [4] [5]. We have proposed an analogous 'form coherence' measure of global processing in the ventral stream [6]. In a functional magnetic resonance imaging (fMRI) experiment, we found that the cortical regions activated by form coherence did not overlap with those activated by motion coherence in the same individuals. Areas differentially activated by form coherence included regions in the middle occipital gyrus, the ventral occipital surface, the intraparietal sulcus, and the temporal lobe. Motion coherence activated areas consistent with those previously identified as V5 and V3a, the ventral occipital surface, the intraparietal sulcus, and temporal structures. Neither form nor motion coherence activated area V1 differentially. Form and motion foci in occipital, parietal, and temporal areas were nearby but showed almost no overlap. These results support the idea that form and motion coherence test distinct functional brain systems, but that these do not necessarily correspond to a gross anatomical separation of dorsal and ventral processing streams.